Sexual Violence Scripts: Comparison of Indonesian Films with United - Florentius Ernesto Louis; Ikhsan Fuady (Persepsi: Communication Journal, 2023)
These days, society has started to accept discussions about sexual assault, instead of being judgmental towards the victim. For this reason, sexual assault became one of the many issues that is frequently talked about in media, one of them being movies. Realizing the differences in the perception towards women’s roles in an advanced country like the United States compared to a much more conservative country like Indonesia, therefore this quantitative content analysis research aims to discover and compare how sexual assault is represented in Indonesian and United States movies. The two main theories that construct this research’s theoretical framework is the social cognitive theory and script theory. The unit of analysis of this research is sexual assault scripts in movies. The research population consists of 5 Indonesian movies and 5 United States movies that brought up the sexual assault issue. The sample was determined using the purposive sampling technique. The results of this research show that even though there are some differences in the representation of sexual assault according to some indicators, there is no significant association between the variables and the countries who made the films.